Perkembangan UMKM Di Indonesia : Peran Pemahaman Akuntansi, Teknologi Informasi dan Sistem Informasi Akuntansi - Fitriani Saragih; Rahmat Daim Harahap; Nurlaila (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine the development of MSMEs in Indonesia which is influenced by several factors including the role of understanding accounting, information technology, and information systems. The sampling technique used a census technique with a total of 100 respondents who were randomly selected. The analytical test tool used is SmartPLS v.3.2.9 with the SEM (Structural Equation Modeling) analysis method. This analysis is a statistical testing technique to describe the simultaneous linear relationship between indicator variables and variables that cannot be measured directly. This research method uses a quantitative approach with explanatory research with measurement models of Convergent Validity, Discriminant validity, Composite reliability, Alpha Cronbach indicators, and statistical hypothesis testing. The results of this study indicate that the P-Values are 0.000 <0.05 so that Accounting Understanding has a positive and significant influence on the development of MSMEs in Indonesia, the P-Values are 0.054 > 0.05 so that the Utilization of Information Technology has no direct and significant influence on The development of MSMEs in Indonesia and the influence of the variable Accounting Information System on the development of MSMEs has a P-Value of 0.001 <0.05 so that the Accounting Information System has a direct and significant effect on the development of MSMEs in Indonesia.